Creative bibliotherapy for post-traumatic stress disorder (PTSD): a systematic review*. Issue 2 (3rd April 2017) - Glavin, Calla E. Y.; Montgomery, Paul
ABSTRACT: Creative bibliotherapy – or the guided reading of fiction or poetry – is used widely in mental healthcare settings. In the UK, partnerships between private organizations, libraries, and the NHS support reading groups for better mental health and social cohesion. In the USA, veterans' reading support groups are common and private lifestyle consultancies offer services that match clients to books for general well-being. Considering the widespread employment of creative bibliotherapy, this systematic review was conducted to explore its effectiveness in reducing symptoms in adults with post-traumatic stress disorder (PTSD). Both randomized and non-randomized trials were included in the extensive search but no high-quality controlled trials were found. Importantly, there is no evidence to suggest harms from the trial designs related to creative bibliotherapy and some low-quality and qualitative studies indicated this intervention may help PTSD symptoms. High quality randomized controlled trials should be conducted urgently.